The Effect of Urban Spatial Form on Energy Efficiency: A Cross-Sectional Study in China - Chen, Zi-gui; Kong, Ling-jun; Wang, Min; Liu, Hang-kai; Xiao, Da-kai; Wu, We-ping (Frontiers in Energy Research, 2021)
Rational planning and optimization of urban spatial form to achieve the goal of energy efficient utilization and carbon emission reduction is one of the important ways to improve energy efficiency. We deconstruct urban spatial form into centrality, aggregation and complexity, and analyze net effect and its heterogeneity of urban spatial form on energy efficiency with OLS, quantile regression model as well as grouped regression model. The results show that the effects of urban spatial centrality and complexity on energy efficiency are nonlinear. For the vast majority of cities, strengthening urban spatial centrality will significantly improve energy efficiency, but the growth rate will gradually decrease. The impact effect of urban complexity on energy efficiency has the characteristics of U-shaped trend with an inflection point value of 0.429. And for the three-quarters of urban samples, enhancing urban spatial complexity will reduce energy efficiency. The positive effect of urban spatial aggregation on energy efficiency is only significant in cities with high quantile for energy efficiency. In terms of urban heterogeneity, the positive effects of spatial centrality and aggregation on energy efficiency are more obvious in megacities with a permanent population of more than 5 million, and the negative effect of spatial complexity on energy efficiency is more obvious in small and medium-sized cities. Whether it is promotion or inhibition, the urban samples with high energy efficiency are more affected by the change of urban spatial form. Optimizing the urban spatial form is one of the important ways to improve the energy efficiency, and the policy setting should give full consideration to the urban heterogeneity and classified policies.